Creative Problem-Solving Tasks and Mathematical Creativity: A Second-Order Construct Approach - Purwati Purwati; Tri Candra Wulandari; Sandha Soemantri (Universitas Papua, 2025)
This study aimed to address a research gap by examining the effect of Creative Problem-Solving Tasks (CPST) on students’ creative self-efficacy and creative thinking ability in solving integer operation problems. A quasi-experimental design with a pretest-posttest non-equivalent control group was employed, involving 60 seventh-grade students from two public junior high schools. Participants were divided into an experimental group (CPST-based instruction) and a control group (conventional instruction). Instruments included a creative self-efficacy questionnaire and an open-ended mathematical creative thinking test contextualized in integer operations. Data were analyzed using independent sample t-tests and confirmatory factor analysis. The t-test results showed significant differences between the experimental and control groups in both self-efficacy scores (t(58) = 11.56, p < 0.001) and creative thinking ability (t(58) = 5.22, p < 0.001). The experimental group demonstrated consistent improvement in the dimensions of fluency, flexibility, and originality. Confirmatory factor analysis supported the structure of mathematical creativity as a second-order construct. These findings indicate that implementing CPST in mathematics instruction significantly enhances students’ confidence and fosters the development of creative thinking simultaneously. The implication of this study highlights the importance of instructional approaches that integrate both affective and cognitive dimensions to support mathematical creativity, particularly in complex topics such as integer operations.